Aspects of Spirituality and Life Satisfaction in Persons With Down Syndrome. (2nd January 2017) - Büssing, Arndt; Broghammer-Escher, Silke; Baumann, Klaus; Surzykiewicz, Janusz
ABSTRACT: In a cross-sectional survey among 65 persons with Down syndrome, the authors intended to identify emotional and behavioral aspects of spirituality that were of importance to them. Feelings of wondering awe, praying, and church attendance were stated rather seldom, whereas many had frequent experiences of gratefulness. Those living without their parents were more in need of concrete personal relationships and relied on transcendent sources of help. Life satisfaction correlated best with feelings that God is at their side. Although the relational aspects of spirituality were of particular importance to those in our sample, it remains uncertain who can support these essential needs when many of them lack reliable family structures.